PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA PEGAWAI DENGAN DIMEDIASI OLEH KEPUASAN KERJA PEGAWAI PADA DINAS PERHUBUNGAN PEMERINTAH KABUPATEN TABANAN - I Made Yudi Anggara; Anak Agung Dwi Widyani; Ni Putu Ayu Sintya Saraswati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2022)
The purpose of this study was to determine the effect of transformational leadership and job satisfaction on the performance of the employees of the Tabanan Regency Government Transportation Service. As for the sample in this study amounted to 80 employees. The results of the study found that 1) Transformational leadership has a positive and significant effect on employee performance, 2) Transformational leadership has a positive and significant effect on job satisfaction, 3) Job satisfaction has a positive and significant effect on employee performance and 4) Job satisfaction can be a mediating variable for the influence of transformational leadership on employee performance.